Morphological and molecular characteristics of Malayfilaria sofiani Uni, Mat Udin & Takaoka n. g., n. sp. (Nematoda: Filarioidea) from the common treeshrew Tupaia glis Diard & Duvaucel (Mammalia: Scandentia) in Peninsular Malaysia - Uni, Shigehiko; Mat Udin, Ahmad Syihan; Agatsuma, Takeshi; Saijuntha, Weerachai; Junker, Kerstin; Ramli, Rosli; Omar, Hasmahzaiti; Lim, Yvonne Ai Lian; Sivanandam, Sinnadurai; Lefoulon, Emilie; Martin, Coralie; Belabut, Daicus Martin; et al. (BMC, 2017)
Background: The filarial nematodes Wuchereria bancrofti (Cobbold, 1877), Brugia malayi (Brug, 1927) and B. timori Partono, Purnomo, Dennis, Atmosoedjono, Oemijati and Cross, 1977 cause lymphatic diseases in humans in the tropics, while B. pahangi (Buckley and Edeson, 1956) infects carnivores and causes zoonotic diseases in humans in Malaysia. Wuchereria bancrofti, W. kalimantani Palmieri, Pulnomo, Dennis and Marwoto, 1980 and six out of ten Brugia spp. have been described from Australia, Southeast Asia, Sri Lanka and India. However, the origin and evolution of the species in the Wuchereria-Brugia clade remain unclear. While investigating the diversity of filarial parasites in Malaysia, we discovered an undescribed species in the common treeshrew Tupaia glis Diard and Duvaucel (Mammalia: Scandentia). Methods: We examined 81 common treeshrews from 14 areas in nine states and the Federal Territory of Peninsular Malaysia for filarial parasites. Once any filariae that were found had been isolated, we examined their morphological characteristics and determined the partial sequences of their mitochondrial cytochrome c oxidase subunit 1 (cox1) and 12S rRNA genes. Polymerase chain reaction (PCR) products of the internal transcribed spacer 1 (ITS1) region were then cloned into the pGEM-T vector, and the recombinant plasmids were used as templates for sequencing. Results: Malayfilaria sofiani Uni, Mat Udin and Takaoka, n. g., n. sp. is described based on the morphological characteristics of adults and microfilariae found in common treeshrews from Jeram Pasu, Kelantan, Malaysia. The Kimura 2-parameter distance between the cox1 gene sequences of the new species and W. bancrofti was 11.8%. Based on the three gene sequences, the new species forms a monophyletic clade with W. bancrofti and Brugia spp. The adult parasites were found in tissues surrounding the lymph nodes of the neck of common treeshrews. Conclusions: The newly described species appears most closely related to Wuchereria spp. and Brugia spp., but differs from these in several morphological characteristics. Molecular analyses based on the cox1 and 12S rRNA genes and the ITS1 region indicated that this species differs from both W. bancrofti and Brugia spp. at the genus level. We thus propose a new genus, Malayfilaria, along with the new species M. sofiani.